Cultured Reed-Sternberg cells HDLM-1 and KM-H2 can be induced to become histiocytelike cells. H-RS cells are not derived from lymphocytes. - Hsu, S. M. (1990)
Two Hodgkin's Reed-Sternberg cell (H-RS) lines, HDLM-1 and KM-H2, have phenotypes and functional properties very similar to those of H-RS cells in tissues. These two types of cells were induced to differentiate with a combination of phorbol ester, retinoic acid, and extracellular matrix. The induced cells displayed the morphology of histiocytes or histiocytelike cells, with a small, round or oval, eccentric nucleus and abundant cytoplasm. In ultrastructural studies, many cytoplasmic projections and rugae were observed. These induced cells exhibited abundant cytoplasmic lysosomal enzymes, such as esterase, acid phosphatase, alpha 1-antitrypsin, or lysozyme. The histiocytic nature of these induced cells was further confirmed by the increased expression of many monocyte/histiocyte markers, including CD11b, CD11c, CD13, CD14, CD15, CD33, CD68, Mac387, and 1E9. In functional tests, the induced cells were shown to produce interleukin-1, tumor necrosis factor, macrophage colony-stimulating factor, and/or prostaglandin E2. Phagocytosis was detected in less than 5% to 10% of the cells when Candida albicans was added to cultures. The results strongly suggest that H-RS cells are related to cells of histiocyte lineage.